2022
DOI: 10.1002/sd.2362
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to sustainable development: Critical social factors influencing the sustainable building development based on Swedish experts' perspectives

Abstract: Sustainable construction plays a major role in sustainable development. However, the investment rate in sustainable buildings has decreased in recent years. Considering that social factors are one of the important factors influencing the sustainable building development, this paper highlighted the most impactful social factors affecting the sustainable building development based on the opinions of the industry experts from Sweden. Therefore, social challenges and barriers to sustainable building development we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…Currently, the world's economic activity and population are expanding swiftly, leading to a spike in environmental deterioration and a growing focus on the issue. The increased prominence of ecological concerns required the studies on the consequences of different ecological policy measures in order to meet SDGs (Dalirazar & Sabzi, 2022). Analyzing the ecological strategy adoption, it is evident that legal legislation, including compulsory rules backed by multiple restrictions, has been primarily applied to avoid the escalation of environmental deterioration (Cheng et al, 2021; Muhammad et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the world's economic activity and population are expanding swiftly, leading to a spike in environmental deterioration and a growing focus on the issue. The increased prominence of ecological concerns required the studies on the consequences of different ecological policy measures in order to meet SDGs (Dalirazar & Sabzi, 2022). Analyzing the ecological strategy adoption, it is evident that legal legislation, including compulsory rules backed by multiple restrictions, has been primarily applied to avoid the escalation of environmental deterioration (Cheng et al, 2021; Muhammad et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Other research studies have shown that the implementation of sustainability principles in the private sector is a serious concern [33], so managers tend to assign sustainability tasks, responsibilities or competences to all occupations, according to their specific tasks [6,34] or market conditions [35][36][37].…”
Section: Perceptions Of the Implementation Of Sustainability Policies...mentioning
confidence: 99%
“…job opportunities, improving participation in creating community capacities, reducing impact on cultural and historical heritage." (Dalirazar & Sabzi, 2022) 4. "Social sustainability is perceived as a sustainable development principle aimed at achieving equality and reducing poverty through job creation and education, empowerment and freedom, preservation of diversity, protection and promotion of human rights, equity and health and safety."…”
Section: "Social Goals [Of Sustainable Development Include] Improving...mentioning
confidence: 99%